Proactive and Predictive Maintenance Strategies and Application for Instrumentation & Control in Oil & Gas Industry - Ngu, Kie Ming; Philip, Nicholas; Sahlan, Shafishuhaza (International Journal of Integrated Engineering, 2019)
Instrumentation & Control Systems have gone through various revolutions in the oil and gas industry. The start of the industry was based on pneumatic controllers, operating with instrument air or instrument gas at 0.2 to 1.0 barg and the Instrument Protective System (IPS) was relay based. This system provided almost zero information or data that can be used to predict failure and had a higher unrevealed failure. The next phase of instrumentation was migration into the electronics era. This allowed for the migration from a pneumatic system to the application of electronics field device operation on 4-20mA connected to Distributed Control System (DCS) and IPS. Further development of 4-20mA communication protocol allowed for the development of digital superimpose communication called Highway Addressable Remote Transducer (HART). The data that is transmitted in HART protocol provides sufficient data and information to predict the health and functionality of the instrumentation. Changes in the maintenance philosophy from reactive maintenances to proactive or predictive maintenances, resulted in reduced downtime by scheduling maintenance to optimize the working window. This work process allows for greater productivity of assets, both human and capital. Dashboards are developed and utilised to alert fault detection and loss of redundancy, whereby data is relayed from DCS and IPS to a web-based system. Available tools being developed in the industry and application of IoT within the industry allows for real-time field device health monitoring and an engine to predict deviations. The strength and weakness of the various proactive or predictive maintenance strategies are compared and summarized, including scope for future research and application in the industry.